Multimodal learning in action: Multiple intelligences transforming inclusive English education in early childhood classrooms - Pratiwi, Widya Rizky (Institut Agama Islam Negeri Kendari, 2026)
This study explores how multimodal learning grounded in MI theory transforms inclusive English education practices in a kindergarten setting. A qualitative case study was conducted in an inclusive kindergarten in Ende Regency, Eastern Indonesia, a geographically peripheral and culturally diverse semi-rural context with limited resources. Participants included three English teachers, a school principal, and a head supervisor involved in inclusive learning. Data were collected through semi-structured interviews, classroom observations, and document analysis, followed by thematic analysis supported by data triangulation. Findings show that MI was implemented as an integrated pedagogical orientation rather than isolated strategies, reflected in multimodal instruction, flexible classroom organization, collaborative teaching, experiential learning, and holistic assessment. These practices enhanced student engagement, social interaction, and language participation among diverse learners.